DETEKSI FINANCIAL STATEMENT FRAUD DENGAN ANALISIS FRAUD PENTAGON PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 – 2017 - Fatihatul Faidah; Titiek Suwarti (Dinamika Akuntansi Keuangan dan Perbankan, 2018)
This study aims to examine the detection of Fraud's Financial Statementusing the pentagon theory. This research was conducted using the variable Financial Stability ,Financial Target, External Pressur, Personal Financial Need, Ineffective Monitoring, Nature of Industry , Rationalization , Capability and Arrogance . The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses a purpose sampling method, so that 44 companies can be used as samples every year. The analytical tool used in this study is logistic regression analysis. The test results show that Nature of Industry has a significant positive effect on financial statement fraud. External Pressure has a significant negative effect on Financial Statement Fraud. While variable Financial Stability, Financial Target , Personal Financial Need, Ineffective Monitoring , Rationalization Capability and Arrogance has no a significant effect on Financial Statement Fraud. Keywords: financial statement, financial stability, financial target, external pressure, nature of industry, personal financial need, ineffective monitoring, rationalization, capability and arrogance